The influence of health-seeking behavior on the incidence and perinatal outcome of umbilical cord prolapse in Nigeria (2010)
Objectives: To determine the influence of health-seeking behavior of urban women in South- West Nigeria on the incidence and perinatal outcome of umbilical cord prolapse (UCP). Methods: A retrospective study comparing two groups of urban women using information extracted from medical records of patients who had UCP, and were managed at the University College Hospital Ibadan, Nigeria from January1st 1995 to December 31st 2005. The data was analyzed using SPSS software (version 15). Analysis included simple tabulation, proportion and comparison of incidence, perinatal morbidity, and mortality of UCP between the two groups of women using Chi-square or Fisher’s exact test. Odds ratio (OR) and 95% confidence intervals (CI) were calculated whenever necessary. P-value of 0.05 or less was statistically significant. Results: Women without prenatal care were more likely to have fetuses with UCP (54, 75%), than in women who had prenatal care (18, 25%). The risk of perinatal death from UCP was higher in women without prenatal care, as compared with those who received prenatal care (OR 3.02, 95% CI: 0.879 to 10.356; P-value = 0.061). The risk of perinatal morbidity and neonatal intensive care admission was also higher among women without prenatal care as compared with women who received prenatal care (OR 4.09, 95% CI: 1.03 to 16.30; P-value = 0.041). The overall perinatal mortality rate in the study population was 403 per 1000 total births, and this was five times more than that of the hospital perinatal mortality rate of 80 per 1000 total births during the study period. The perinatal mortality rate was higher among women without prenatal care, 463 per 1000 total births, as compared with 222 per 1000 total births in women who received prenatal care. Perinatal death before arrival at the hospital is less likely to occur in women with prenatal care when compared with women without prenatal care (OR 0.0635; 95% CI: 0.0052 to 0.776; P-value = 0.03). Conclusion: A high index of suspicion and an identification of risk factors, with early diagnosis, prompt intervention, and provision of health care facilities can reduce the incidence and poor outcome of UCP in developing countries